2016 45th International Conference on Parallel Processing (ICPP) 2016
DOI: 10.1109/icpp.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Matrix Format Selection with Multiclass SVM for SpMV on GPU

Abstract: Sparse Matrix-Vector Multiplication (SpMV) kernel dominates the computing cost in numerous scientific applications. Many implementations based on different sparse formats were proposed recently for this kernel on the GPU side. Since the performance of these sparse formats varies significantly according to the sparsity characteristics of the input matrix and the hardware specifications, no one of them can be considered as the best one to use for every sparse matrix. In this paper, we address the problem of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 15 publications
1
42
0
Order By: Relevance
“…Hence, we remove the cases where COO format is the best format. Similar observation is made by Benatia et al [8], where they avoid the COO format in their study.…”
Section: A Discussion On Coo Formatsupporting
confidence: 89%
See 4 more Smart Citations
“…Hence, we remove the cases where COO format is the best format. Similar observation is made by Benatia et al [8], where they avoid the COO format in their study.…”
Section: A Discussion On Coo Formatsupporting
confidence: 89%
“…However, this feature set is not sufficient in capturing the spatial patterns associated with sparse matrices. As an example, previous studies [8], [9] have addressed this issue by introducing additional features that are shown in feature set 2. The feature set 2 and 3 requires a scan on the entire matrix resulting in a time complexity of O(nnz) .…”
Section: Sparse Matrix Features For Machine Learningmentioning
confidence: 99%
See 3 more Smart Citations